2017
DOI: 10.22146/gamaijb.15619
|View full text |Cite
|
Sign up to set email alerts
|

Female Directors and Firm Performance: Evidence from UK Listed Firms

Abstract: Abstract:The impact of female directors on firm performance has lacked consistency in the previously conducted empirical studies, which may be due to the endogeneity problem, or certain characteristics (i.e. governance, industry, competition). This study examines the relationship between female directors and firm performance by addressing those problems. This study analyses all non-financial UK listed firms during the period 2004-2012 and employs several econometric models. The regression results indicate that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 40 publications
3
19
0
7
Order By: Relevance
“…The results are in line with those reported previously (e.g., [2,12]), which also showed that a significant positive association between gender diversity on the boards of directors and firm performance is not robust. However, the aforementioned studies did document a significant relationship for subsamples of their population: companies with weak corporate governance [2] and small companies assumed to be poorly governed [12] and to have more flexibility in assigning female directors on the boards. Following the same rationale, we investigate the validity of our hypothesis across types of companies (profit/loss-companies, premium/standard tier listed firms, financial/nonfinancial companies).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The results are in line with those reported previously (e.g., [2,12]), which also showed that a significant positive association between gender diversity on the boards of directors and firm performance is not robust. However, the aforementioned studies did document a significant relationship for subsamples of their population: companies with weak corporate governance [2] and small companies assumed to be poorly governed [12] and to have more flexibility in assigning female directors on the boards. Following the same rationale, we investigate the validity of our hypothesis across types of companies (profit/loss-companies, premium/standard tier listed firms, financial/nonfinancial companies).…”
Section: Resultssupporting
confidence: 92%
“…For instance, Vafaei et al [31] following Adams and Ferreira's [2] strategy of addressing methodological weaknesses in previous studies, document a significant positive impact of gender-diverse boards of directors on financial performance (proxied by ROA, ROE, Tobin's Q and the ratio of cash flow from operations to total assets) based on a sample of Australian top 500 companies listed during 2005-2011. Pasaribu [12], after controlling for endogeniety, provided for contrary results on a sample of non-financial companies listed on London Stock Exchange during 2004-2012. However, according to a size-based analysis, Pasaribu [12] found that the presence of female directors on boards is positively correlated with financial performance for small companies but not for large ones, which was explained, in a similar manner to Adams and Ferreira [2], based on over-monitoring problems experienced by large companies with strong governance after appointing female directors but also based on the flexibility small companies have on appointing female directors.…”
Section: Literature Reviewmentioning
confidence: 92%
See 1 more Smart Citation
“…Study by Indarti and Langerberg (2004) on the contrary found no relation between gender and business success. Meanwhile study by Prijadi and Desiana (2017) indicates in the case of Indonesia, SMEs run by female entrepreneur will have higher sales but not higher profit and in the case of UK small listed firm, female directors has positive effect on firm performance (Pasaribu, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…As well as having a positive impact on financial performance, studies found a direct positive link between female board directors and dividend performance, proposing that more companies need to seek out a greater number of female directors (Post & Byron, 2015;Pucheta-Martinez & Bel-Oms, 2016;Chen, Leung & Goergen, 2017). Not all studies on the relationship have been positive and a number of studies have found either no evidence of improved financial performance or in fact have reported a potential negative relationship with the presence of women on boards (Rose, 2007;Adams & Ferreira, 2009;Pasaribu, 2017).…”
Section: Literature History and Empirical Evidencementioning
confidence: 99%